2022
DOI: 10.1177/1357633x221076695
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Assessment Clinic: A virtual fracture clinic model that delivers on its PROMise!

Abstract: Background The use of virtual fracture clinics across the United Kingdom and Ireland is growing and have been shown in an increasing number of studies to be safe, cost-effective and associated with good functional outcomes and patient satisfaction rates for certain fracture types. Initially pioneered at Glasgow Royal Infirmary, many centres have adopted similar templates, or variations of, and the overall aim of this study was to assess functional outcomes and injury recovery satisfaction rates of patients dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The remaining study by Aboelmagd et al assessed the use of a VFC for suspected scaphoid fractures ( 28 ) which often have minimal radiological evidence on diagnosis but have a high morbidity if missed due to the risk of avascular necrosis ( 31 ). The sex distribution was close to evenly split with a slight male predominance ( 25 28 ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The remaining study by Aboelmagd et al assessed the use of a VFC for suspected scaphoid fractures ( 28 ) which often have minimal radiological evidence on diagnosis but have a high morbidity if missed due to the risk of avascular necrosis ( 31 ). The sex distribution was close to evenly split with a slight male predominance ( 25 28 ).…”
Section: Resultsmentioning
confidence: 93%
“…Five of the studies reported on the time between initial presentation and review in the VFC and all of these were within 72 h, indicating high compliance with the BOAST 7 guidelines ( 25 , 27 – 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(6) As the strain on healthcare resources is increasing, addressing these issues in non-operative management may be essential in sustaining high-quality orthopedic trauma care. (7) The Virtual Fracture Care (VFC) model has emerged as a reorganizational solution for non-operative management musculoskeletal extremity injuries, adopted by various countries in several variations (8)(9)(10)(11)(12). Typically, the VFC model comprises two components: 1) a Direct Discharge protocol facilitating the direct discharge of patients with uncomplicated and stable injuries from the ED, and 2) a VFC review protocol, referring patients in need of further treatment to the most suitable healthcare professional.…”
Section: Introductionmentioning
confidence: 99%